Analysis of non-Newtonian lubricated textured contact for mixed slip/no-slip configuration considering cavitation. (May 2019) - Pratomo, A W; Muhammad; Tauviqirrahman, M; Jamari, J; Bayuseno, A P
Abstract: The increasing use of non-Newtonian fluids as lubricants has received much attention due to their high shear. The present study explores a lubrication mechanism in lubricated textured contact for mixed slip/no-slip pattern considering cavitation. The effect of texturing depth on the bearing performance is also investigated. The numerical method based on commercial CFD (computational fluid dynamic) software is carried out to analyze the tribological characteristics (i.e., hydrodynamic pressure distribution) of lubricated textured contact. To model slip, the enhanced user-defined-function (UDF) in the FLUENT® package is developed. The analysis results show that giving textures as well as a slip to one of the parallel sliding surfaces can generate significant hydrodynamic pressure to affect the load support. The increase in the load support is also indicated by increasing the streamline recirculating flow. Besides, numerical results suggest that cavitation modeling has a significant effect on performance. Ignoring cavitation leads to less accurate results.